Application of fuzzy optimization in energy saving - Silva, Luiz Eduardo Borges; Torres, Germano Lambert; Reis, Luiz Octávio Mattos; Haddad, Jamil (Revista Ciências Exatas, 2008)
In many power system problems, the use of optimization techniques has been important to reduce costs and losses of the system. One of the most important points in process is the computational cost to find the best solution. Sometimes, this cost may comprise the use of a technique to solve a problem. Number of constraints, number of variables and poor convergence speed are some examples of computational cost. This paper presents a development using fuzzy optimization process. This paper starts with theoretical aspects of the fuzzy optimization process and then, an example using power system energy saving is presented.